2016
DOI: 10.1038/eye.2016.263
|View full text |Cite
|
Sign up to set email alerts
|

Inverted internal limiting membrane flap technique as a useful procedure for macular hole-associated retinal detachment in highly myopic eyes

Abstract: PurposeTo determine whether the inverted internal limiting membrane (ILM) flap technique contributes to high reattachment and closure rates in patients with macular hole-associated retinal detachment (MHRD).Patients and methodsIn all, 15 eyes of 15 patients with MHRD undergoing 25-gauge pars plana vitrectomy with the inverted ILM flap technique or ILM peeling. The patients were divided into the inverted ILM flap technique group (6 eyes) and ILM peeling group (9 eyes). The logarithm of minimal angle of resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 33 publications
1
69
0
3
Order By: Relevance
“…The shortest follow-up duration was 6 months in 3 studies [ 23 – 25 ], the follow-up duration was 12 months in 1 study [ 22 ]. 25-gauge vitrectomy was performed in 3 studies [ 22 24 ], 23-gauge vitrectomy was performed in 1 study [ 25 ]. To visualize ILM, brilliant blue G was used in 3 studies [ 22 24 ], indocyanine green (ICG) was used in 1 study [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The shortest follow-up duration was 6 months in 3 studies [ 23 – 25 ], the follow-up duration was 12 months in 1 study [ 22 ]. 25-gauge vitrectomy was performed in 3 studies [ 22 24 ], 23-gauge vitrectomy was performed in 1 study [ 25 ]. To visualize ILM, brilliant blue G was used in 3 studies [ 22 24 ], indocyanine green (ICG) was used in 1 study [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…25-gauge vitrectomy was performed in 3 studies [ 22 24 ], 23-gauge vitrectomy was performed in 1 study [ 25 ]. To visualize ILM, brilliant blue G was used in 3 studies [ 22 24 ], indocyanine green (ICG) was used in 1 study [ 25 ]. C 3 F 8 gas tamponade was applied in 4 studies, SF 6 gas tamponade was used in 2 studies [ 22 , 24 ], Silicone oil tamponade was used in 1 study [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept was confirmed firstly by Michalewska et al in larger macular hole (MH) to facilitate the healing process and now has been extended for use in treating MHRD [2]. However, vitreoretinal surgeons are still asking, BIs the inverted ILM flap technique still a preferable option for MHRD?^Previous direct comparison studies have suggested contradictory results [3][4][5][6]. On this issue, Wakabayashi et al reported that the inverted ILM insertion technique seems to improve the anatomical results in terms of MH closure rate rather than the functional results of MHRD despite there being a tendency for better postoperative visual acuity in the inverted ILM insertion group.…”
mentioning
confidence: 76%
“…EMB have also been used in the management of MRS with a number of studies recommending a combination of macular buckling and vitrectomy in order to address both inner traction and the posterior staphyloma [57][58][59]. Recent published data, however, using a variation on ILM peeling have demonstrated macular hole closure rates of 80-100% and retinal reattachment rates of 100% using the inverted ILM flap technique, compared to 36-55% and 55-91%, respectively, using standard ILM peeling in cases with MHRD [60,61].…”
Section: Discussionmentioning
confidence: 99%